Respuesta :
The equation that results from applying the tangent segment theorem to the given figure is; x(2x + 4) = (x + 2)²
What is the correct equation?
According to the secant and tangent segment theorem, the square of the tangent line is equal to the product of the secant segments. This is;
Tangent² = whole secant segment × External secant segment
DE² = AD × BD
We are given that;
DE = x
AD = 2x + 4
BD = x + 2
Thus, we have;
x(2x + 4) = (x + 2)²
Read more about segment theorem at; https://brainly.com/question/9330100